Vimentin restrains regulatory T-cell suppression of graft-versus-host disease - McDonal-Hyman, C; Muller, J; Loschi, M; Thangavelu, G; Saha, A; Kumari, S; Reichenbach, D; Smith, M; Zhang, G; Loschi, M; Koehn, BH; Lin, J; et al. (American Society for Clinical Investigation, 2018)
Regulatory T-cells (Treg) are critical for maintaining immune homeostasis. However, current Treg immunotherapies do not optimally treat inflammatory diseases in patients. Understanding the cellular processes that control Treg function may allow for the augmentation of therapeutic efficacy. In contrast to activated conventional T-cells, where protein kinase C-T (PKC-T) localizes to the contact-point between T-cells and antigen-presenting cells, in Treg, PKC-T localizes to the opposite end of the cell in the distal pole complex (DPC). Here, using a phosphoproteomic screen, we identified the intermediate filament vimentin as a PKC-T phosphotarget and show that vimentin forms a DPC superstructure on which PKC-T accumulates. Treatment of Treg with either a clinically relevant PKC-T inhibitor or vimentin siRNA disrupted vimentin and enhanced Treg metabolic and suppressive activity. Moreover, vimentin-disrupted Treg were significantly better than controls in suppressing alloreactive T-cell priming in graftversus-host disease, and graft-versus-host disease lethality. Interestingly, vimentin disruption augmented suppressor function of PKC-T-deficient Treg. This suggests that enhanced Treg activity after PKC-T inhibition is secondary to effects on vimentin, not just PKC-T kinase activity inhibition. Our data demonstrated that vimentin is a key metabolic and functional controller of Treg activity, and provide proof-of-principle that disrupting vimentin is a feasible, translationally relevant method to enhance Treg potency.